Experimental QR code optical encryption: noise-free data recovering - Barrera, John Fredy (2014)
We report, to our knowledge for the first time, the experimental implementation of a quick response (QR) code as a “container” in an optical encryption system. A joint transform correlator architecture in an interferometric configuration is chosen as the experimental scheme. As the implementation is not possible in a single step, a multiplexing procedure to encrypt the QR code of the original information is applied. Once the QR code is correctly decrypted, the speckle noise present in the recovered QR code is eliminated by a simple digital procedure. Finally, the original information is retrieved completely free of any kind of degradation after reading the QR code. Additionally, we propose and implement a new protocol in which the reception of the encrypted QR code and its decryption, the digital block processing, and the reading of the decrypted QR code are performed employing only one device (smartphone, tablet, or computer). The overall method probes to produce an outcome far more attractive to make the adoption of the technique a plausible option. Experimental results are presented to demonstrate the practicality of the proposed security system.